Disruption, worries and autonomy in the everyday lives of adolescents with type 1 diabetes and their family members: A qualitative study of intrafamilial challenges. Issue 23 (1st October 2020) - Overgaard, Mathilde; Lundby‐Christensen, Louise; Grabowski, Dan
Abstract: Aim: To explore daily life with type 1 diabetes in families with an adolescent with type 1 diabetes. Background: Management of adolescent type 1 diabetes is carried out in the context of everyday life, thus involving and affecting the entire family. Type 1 diabetes causes disruption of family life, but the specific experiences and challenges of adolescents with type 1 diabetes, siblings and parents are not well‐explored. Specifically, research is lacking on the siblings' experience of adolescents with type 1 diabetes. Design: A qualitative design using participatory workshops. Methods: A sample of 21 families comprising adolescents with type 1 diabetes (aged 8–18) ( N = 20), their parents ( N = 29) and siblings ( N = 10) participated in four workshops exploring everyday life in families with adolescent diabetes from the perspective of all family members. Data were analysed using systematic text condensation. The COREQ checklist was used preparing the manuscript. Results: Family life with type 1 diabetes was characterised by three overarching themes: (a) the perpetual challenges and disruptive nature of life with diabetes, (b) different ways of worrying about diabetes and (c) diabetes autonomy and emancipation from parents. All family members' lives were marked by these aspects, however in different ways and to varying degrees. Conclusions: Our findings emphasise that type 1 diabetes is indeed a family illness affecting all family members. The study provides insight into the unique experiences of adolescents with diabetes, their parents and siblings, all of whom encounter diabetes‐related challenges in their daily lives. Relevance to clinical practice: The findings call for the inclusion of all family members of adolescents with type 1 diabetes in both research and healthcare practice. Family‐oriented approaches targeting adolescents with diabetes as well as their parents and siblings will enable provision of nursing care that can meet the needs of the entire family.